Music Composition Training for Indonesian School Students in Kuala Lumpur in Preparation for FLS2N Competition Among Indonesian Schools Abroad - Dody Mohamad Kholid; Toni Setiawan Sutanto; Fensy Sella (International Journal of Education and Digital Learning (IJEDL), 2025)
This training activity aims to train students' music skills in preparation for the National Student Art Competition Festival which is a program of the Indonesian government. FLS2N (Festival Lomba Seni Siswa Nasional) is an event organized by the Indonesian Ministry of Education and Culture to facilitate students throughout Indonesia, including students in Indonesian schools abroad, in developing their musical talents and interests. The methods used include regular rehearsals, collaboration between participants, and public performances to build experience. The subjects of this research are school students of all levels who are prepared to represent the school in FLS2N activities. The results of this training are expected to not only improve the quality of student performances at FLS2N, but also foster interest and appreciation for music in the context of Indonesian culture. This training contributes to the development of students' abilities and character as a creative and talented next generation. Service activities through Indonesian music training in Indonesian schools in Kuala Lumpur Malaysia are not only about learning music, but also about enriching students' experiences, strengthening cultural identity, and promoting cooperation between nations.